Improvement of the Elevated Tryptase Criterion to Discriminate IgE- From Non–IgE-Mediated Allergic Reactions. (August 2018) - Gastaminza, Gabriel; Lafuente, Alberto; Goikoetxea, Maria Jose; D'Amelio, Carmen M.; Bernad-Alonso, Amalia; Vega, Olga; Martinez-Molina, Juan Ambrosio; Ferrer, Marta; Nuñez-Cordoba, Jorge M.
Abstract : BACKGROUND: Differentiating between immunoglobulin E (IgE)-dependent and IgE-independent hypersensitivity reactions may improve the etiologic orientation and clinical management of patients with allergic reactions in the anesthesia setting. Serum tryptase levels may be useful to discriminate the immune mechanism of allergic reactions, but the diagnostic accuracy and optimal cutpoint remain unclear. We aimed to compare the diagnostic accuracy of tryptase during reaction (TDR) alone and the TDR/basal tryptase (TDR/BT) ratio for discriminating IgE- from non–IgE-mediated allergic reactions, and to estimate the best cut point for these indicators. METHODS: We included 111 patients (45% men; aged 3–99 years) who had experienced an allergic reaction, even though the allergic reaction could be nonanaphylactic. Allergy tests were performed to classify the reaction as an IgE- or non–IgE-mediated one. The area under the curve (AUC) of the receiver operating characteristic analysis was performed to estimate the discriminative ability of TDR and TDR/BT ratio. RESULTS: An IgE-mediated reaction was diagnosed in 49.5% of patients, of whom 56% met anaphylaxis criteria. The median (quartiles) TDR for the IgE-mediated reactions was 8.0 (4.9–19.6) and 5.1 (3.5–8.1) for the non–IgE-mediated ( P = .022). The median (quartiles) TDR/BT ratio was 2.7 (1.7–4.5) in IgE-mediated and 1.1 (1.0–1.6) in non–IgE-mediated reactions ( P < .001). The TDR/BT ratio showed the greatest ability to discriminate IgE- from non–IgE-mediated reactions compared to TDR (AUC TDR/BT = 0.79 [95% confidence interval (CI), 1.1–2.2] and AUC TDR = 0.66 [95% CI, 1.1–2.2]; P = .003). The optimal cut point for TDR/BT (maximization of the sum of the sensitivity and specificity) was 1.66 (95% CI, 1.1–2.2). CONCLUSIONS: The TDR/BT ratio showed a significantly better discriminative ability than TDR to discriminate IgE- from non–IgE-mediated allergic reactions. An optimal TDR/BT ratio threshold of approximately 1.66 may be useful in clinical practice to classify allergic reactions as IgE- or non–IgE-mediated.